Analisis Kode Sastra Dalam Puisi Orang-Orang Miskin Oleh WS Rendra - Yulsafli Yulsafli; Sariakin Sariakin (LPPM Institut Pendidikan Nusantara Global, 2025)
This research aims to describe the literary code contained in the poem Orang Orang Miskin by WS Rendra. The method used is descriptive qualitative with a semiotic approach, namely the study of signs and marking systems in literary works. In this context, poetry is understood as a text that is full of symbols, indices and icons that represent certain meanings. The research results show that this poem contains 26 symbols, 14 indexes and 8 icons. The significant number of indexes and icons shows that this poem has a depth of meaning that requires critical and interpretive reading. This poem raises universal themes such as social justice, poverty and humanity, and emphasizes the importance of caring for the poor. Indifference towards them is not only a social problem, but can also inspire readers' faith and nationalism. Therefore, understanding the code system in this poetry is the key to capturing the moral and ideological messages that the poet wants to convey.